The Development of Visible-Light Organic Photocatalysts for Atom Transfer Radical Polymerization via Conjugation Extension - Hui Shao; Runzhi Long; Hui Xu; Pan Sun; Guangrong Wang; Yuanming Li; Saihu Liao (Molecules, 2024)
This work aimed to develop organic photocatalysts (PCs) that could mediate organocatalytic atom transfer radical polymerization (O-ATRP) under visible light. Through the core-modification of known chromophoric structures and ring-locking to reach a conjugation extension, annulated N-aryl benzo[kl]acridines were identified as effective visible light-responsive photocatalysts. The corresponding selenium-doped structure showed excellent performance in the O-ATRP of methacrylates, which could afford polymer products with controlled molecular weights and low dispersities under the irradiation of visible light at a 100 ppm catalyst loading.